2013
DOI: 10.1007/s00227-013-2232-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, processes and vulnerability of Southern Ocean benthos: a decadal leap in knowledge and understanding

Abstract: In the Southern Ocean, that is areas south of the Polar Front, long-term oceanographic cooling, geographic separation, development of isolating current and wind systems, tectonic drift and fluctuation of ice sheets amongst others have resulted in a highly endemic benthic fauna,\ud which is generally adapted to the long-lasting, relatively stable environmental conditions. The Southern Ocean benthic ecosystem has been subject to minimal direct anthropogenic impact (compared to elsewhere) and thus presents unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
69
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 163 publications
0
69
0
1
Order By: Relevance
“…As a consequence, patterns of extant and fossil biodiversity are almost completely unknown in the deep sea of this region (e.g. Kaiser et al, 2013), in contrast to the North Atlantic and (in a smaller scale) to the Arctic Ocean, where most deep-sea sampling has taken place (e.g. Levin and Gooday, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, patterns of extant and fossil biodiversity are almost completely unknown in the deep sea of this region (e.g. Kaiser et al, 2013), in contrast to the North Atlantic and (in a smaller scale) to the Arctic Ocean, where most deep-sea sampling has taken place (e.g. Levin and Gooday, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason early predictions suggested that the majority of benthic fauna within Antarctic waters would be endemic to the Southern Ocean (Ekman, 1953;Hedgpeth, 1969). Endemism has since been observed in many major taxonomic groups based on species records from mostly morphological species identification (see reviews Dell, 1972;Arntz et al, 1997;Clarke and Johnston, 2003;Thorpe et al, 2007;De Broyer and Danis, 2011;Brandt et al, 2012;Kaiser et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Due to sampling bias knowledge of SO deep-sea benthos is still low in comparison with data from the shelf, but recent expeditions have documented that the fauna can be rich and abundant, yet with mostly patchy distributions (Clarke and Johnston, 2003;Kaiser et al, 2013). Almost nothing is known about the deep-sea life in the region of the SPF, but the few stations sampled revealed low abundances of benthic organisms (e.g.…”
Section: Introductionmentioning
confidence: 94%